THE URGENCY OF ARTIFICIAL INTELLIGENCE CODE OF ETHICS - Sitabuana, Tundjung Herning; Sanjaya, Dixon; Amri, Ibra Fulenzi; Nethan, Nethan (Indonesia Law Review, 2024)
The era of artificial intelligence has become a characteristic of industrial era 5.0 which has been used in various aspects. Potential economic value of AI has driven various forms of AI innovation development. Exploration of AI tends to override negative impacts of such developments. The emergence of ethical issues with presence of AI encourages the need for a law-based approach to establishing ethical standards to protect entire Indonesian nation. Therefore, this research was conducted to examine urgency for an AI code of ethics. This paper will normatively describe data qualitatively to answer urgency and development of AI code of ethics in doctrinal and regulative contexts, including comparisons of countries that apply ethical code. Phenomenon of emergence of AI has given rise to systemic ethical problems that are both incidental and existential related to humans. Due to disruptive threat of AI, it encourages countries to formulate ethical standards regulatory models. European Union and China have AI ethical guidelines within their legal frameworks although their characteristics differ. Meanwhile, Indonesian legal system doesn’t yet have tools that specifically regulate AI ethics. Weaknesses in regulating AI related to scope of AI, legal harmonization, and weak government commitment and competence. To regulate AI Ethics substantially and formally can be formulated in many variants based on categorization of ethical principles nature, implementation of ethical principles, forming institutions, nature and type of regulations, normative power, and scope of AI impact. New legal instruments are needed based on this categorization.